IMPLEMENTASI HAK TERSANGKA UNTUK MEMPEROLEH BANTUAN HUKUM PADA TINGKAT PENYIDIKAN DI WILAYAH HUKUM POLDA BALI - SARASWATI, PUTU SEKARWANGI (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013)DO - 10.24843/JMHU.2013.v02.i02.p05, 2013)
Legal aid is very essential in creating a fair life and protect human rights, legal aid which aims to protect the rights of the community in terms of legal issues to avoid snagging of all kinds of actions that may harm or arbitrary action officers law enforcement. Based on the theory of the legal system (Legal System Theory) of Lawrence M. Friedman that the enactment of the law is affected by elements such as legal structures (legal structure), the substance of the law (a legal substance), and the culture of law (legal culture), so that the implementation of the right of the accused to obtain legal aid at the level of investigation can be seen from the legal system itself . The procedure to grant legal aid to the accused can be seen in Article 54, Article 55, Article 56 of the Criminal Procedure Code. Based on the results of research in the field, the investigator always offer the right of suspects to legal counsel and accompanied, but the suspect did not use his right so that the investigator make an official report signed by the suspect showed the suspect the reason is not accompanied by legal counsel.
Keywords: Suspect Rights, Legal Aid, Investigation